2019
DOI: 10.1590/1678-992x-2017-0158
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of coffee plant water consumption based on the SEBAL algorithm

Abstract: Awareness of evapotranspiration (ET) and crop coefficient (K c) is necessary for irrigation management in coffee crops. ET and K c spatial variabilities are disregarded in traditional methods. Methods based on radiometric measurements have potential to obtain these spatialized variables. The K c curve and spatial variability of actual evapotranspiration (ET a) were determined using images from Landsat 8 satellite. We used images of young and adult coffee plantations from OLI (Operational Land Imager) and TIRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The studies carried out by [8] reached values of LAI at the upper part of the plant of 1.78 and of 6.5, on average, at the lower portion. In another study, [47] concluded that the LAI value was between 0 and 6.…”
Section: Lai Obtained By the Uavmentioning
confidence: 99%
“…The studies carried out by [8] reached values of LAI at the upper part of the plant of 1.78 and of 6.5, on average, at the lower portion. In another study, [47] concluded that the LAI value was between 0 and 6.…”
Section: Lai Obtained By the Uavmentioning
confidence: 99%
“…The knowledge of crop evapotranspiration (ET) is critical for irrigation management (Gheysari et al, 2017). At field level, ET can be measured using conventional techniques, such as the Bowen ratio, eddy covariance, soil water balance and lysimetric procedure (Costa et al, 2018;Gharsallah et al, 2013). However, these techniques are complex, costly, and require specific equipment and are thus generally applied only in scientific research (Gharsallah et al, 2013) and limited to homogeneous surfaces (Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At field level, ET can be measured using conventional techniques, such as the Bowen ratio, eddy covariance, soil water balance and lysimetric procedure (Costa et al, 2018;Gharsallah et al, 2013). However, these techniques are complex, costly, and require specific equipment and are thus generally applied only in scientific research (Gharsallah et al, 2013) and limited to homogeneous surfaces (Costa et al, 2018). On the other hand, over heterogeneous surfaces, water consumption can be monitored with the scintillation technique (Ezzahar et al, 2007) and especially using ET models/algorithms, based on remote sensing data.…”
Section: Introductionmentioning
confidence: 99%
“…Its application is recommended for water resources management due to its ability to provide high resolution estimates of ET [27,43]. Although most SEBAL applications were performed in arid and temperate regions [17,44,45], its use in tropical climates also yielded accurate estimations [46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%